Golidocitinib was used for the first time to treat refractory NK-Large Granular lymphocytic leukemia with a STAT3 mutation, accompanied by hemolytic anemia: a case report - Hao, Hongyuan; Yuan, Chenglu; Zhang, Chen; Jian, Jimo (Frontiers in Immunology, 2025)
BackgroundNK-large granular lymphocytic leukemia (NK-LGLL) is a rare clonal lymphoproliferative disease of natural killer (NK) cells. In refractory cases, traditional chemotherapy regimens and immunosuppressive drugs often prove ineffective. Hematopoietic stem cell transplantation (HSCT) offers the opportunity to rebuild the immune system, but carries significant risks, including graft-versus-host disease (GVHD). Consequently, alternative therapeutic strategies need to be investigated. A recent study published in The Lancet reported on the use of golidocitinib in the treatment of relapsed or peripheral T-cell lymphoma. Notably, this represents the first clinical report demonstrating the efficacy of golidocitinib in managing intractable NK-large granular lymphocytic leukemia.Case presentationIn this study, we present a case of a 53-year-old male with NK-LGLL who achieved successful therapeutic outcomes with golidocitinib administration. The patient had a documented history of chronic gastritis and was admitted with symptoms of fatigue and chest tightness. Despite receiving various treatments such as methotrexate, cyclosporin, cyclophosphamide, and thalidomide, the patient exhibited treatment refractoriness. However, after initiating treatment with golidocitinib, the patient’s blood count improved remarkedly after a single treatment cycle, obviating the need for blood transfusions. The patient maintained golidocitinib treatment without experiencing any serious complications. This is the first reported case demonstrating the efficacy of golidocitinib therapy in treating NK-LGLL.ConclusionThis case highlights the clinical relevance of golidocitinib in developing novel therapeutic strategies for NK-LGLL. Moreover, this treatment option presents the potential as either a bridging therapy or alternative to allo-HSCT.